SUSTAINABILITY OF TEACHERS’ TRAINING PROGRAM TO PREPARING STEM BASED LEARNING IMPLEMENTATION IN INDONESIA - Albert Efendi Pohan; Alpino Susanto; Tubagus Pamungkas; Muhammad Faizal Abd. Ghani; Samsuddin Siregar; Desi Rahmawati; Mubik Ihtajuddin Hammas; Reny Trisusanti; Agusmal; Syafrizal (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Science, Technology, Engineering, and Math (STEM) based education serves as effective teaching method for developing students' critical thinking, creative, and problem-solving skills. However, implementing STEM learning in various parts of Indonesia, including at primary and secondary level at Karimun Regency, remains challenging. Pre-training observational data revealed that none of the 135 surveyed elementary and middle school teachers in Karimun Regency had received training in applying STEM-based learning to their teaching practices. In fact, teachers do not know and understand learning with STEM approach at primary and secondary levels. This international community service initiative offers training on applying STEM-based learning to elementary and middle school teachers in Karimun Regency, Province of Riau Kepulauan, Indonesia. This program conducted during the 2024-2025 academic year, involved 150 teachers. The training measurement outcomes show that: 1) The training program for creating STEM-based lesson plans was successful. 2) Teachers understand STEM-based learning concepts and can develop lesson plans that meet STEM-based learning criteria. This training program enables to incorporate STEM-based learning in their schools, thereby enhancing students' critical thinking, creativity, and problem-solving abilities. The results of this program contribute to teachers, school management, and the government to prioritize sustainability training to increase the effectiveness of STEM implementation.